The school story - Clements, Andrew, 1949-2019- (Simon & Schuster Books for Young Readers, 2001)
After twelve-year-old Natalie writes a wonderful novel, her friend Zoe helps her devise a scheme to get it accepted at the publishing house where Natalie's mother works as an editor.